Exploring Crime Rate through the Lens of Poverty and Education in Indonesia: Evidence from Panel Data Approach - FITRIYANI, Fitriyani; ZULHAM, Teuku; SURIANI, Suriani; SAPUTRA, Jumadil; NOVINDA, Mhd Yavishan; ISMAWAN, Indra; ALTHAF, Fillah Ramadhan (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).14, 2025)
This study investigates the determinants of crime rates across 34 Indonesian provinces from 2007 to 2023, with a particular focus on the impact of poverty and education. Employing a panel data approach with an Autoregressive Distributed Lag (ARDL) model, the research reveals significant long-term and short-term relationships between these factors and crime rates. The findings indicate that poverty rates have a significant positive long-term effect on crime rates, whereas the influence of average years of schooling is not statistically significant in the long run. In the short term, both the change in crime rates from the previous period and the change in average years of schooling from the two prior periods significantly affect current crime rate fluctuations. The presence of significant error adjustment coefficients suggests a cointegration relationship or long-term equilibrium among the model variables. Based on these results, this study recommends that policymakers and stakeholders develop strategies aimed at poverty reduction and improved access to quality education as a potential means to mitigate crime rates in Indonesia. Furthermore, the research emphasizes the need for additional investigation of other potential contributing factors, such as family structure, peer group influence, and availability of legal and illegal opportunities, to enhance the effectiveness and sustainability of crime prevention and reduction efforts.